Pathology - Montenegro, Mário Rubens [UNESP]; Franco, Marcello [UNESP] (Taylor & Francis, 2018)
Motta was the first pathologist to publish a systematic description of the morphological alterations observed in patients with paracoccidioidomycosis. The great majority of reports on the pathology of paracoccidioidomycosis in man are based on clinical and radiological descriptions of the lesions and on the study of biopsies obtained when the disease is well established. P. brasiliensis isolates vary in their growth curves, ultrastructural features, and antigen composition. These findings indicate that paracoccidioidomycosis may be caused by different strains of P. brasiliensis. Lungs are involved in the majority of patiens with paracoccidioidomycosis. The initial alterations occur at the alveolar level and may be exudative or granulomatous in nature. The frequent oro- or pharyngeal lesions of paracoccidioidomycosis begin as groups of small papules surrounded by a congested halo. Occasionally paracoccidioidomycosis appears to cause mild, nonspecific symptoms, which can be diagnosed as a flu-like syndrome.